Medication related osteonecrosis of the jaws: Prospective cohort study analysing the aetiology, microbiology, and response to surgical debridement with adjunctive leucocyte and platelet rich fibrin (L-PRF) - HALLEY, DAPHNE (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2018)
Background Bisphosphonates and RANK ligand inhibitors are antiresorptive medications which are prescribed for the treatment of osteoporosis and bone metastases. These medications inhibit osteoclastic action thereby reducing bone turnover, which significantly improves quality of life in the context of oncology patients and greatly reduces the incidence of fragility fractures for osteoporotic patients. An adverse side effect that can develop as a result of these drugs is medication related osteonecrosis of the jaws (MRONJ), which can affect quality of life, resulting in profound morbidity. Since the emergence of this disease entity in 2003, research efforts have been focused on enhancing our understanding of the aetiology, pathogenesis and management of MRONJ. However, treatment of this condition can be difficult, posing significant challenges for clinicians. Conservative management has been the mainstay for treating MRONJ, and in the palliation of symptoms. However, more recent studies adopting a surgical approach appear to yield superior curative rates. The aim of this study was to identify common risk factors in the aetiology and pathogenesis of MRONJ, and evaluate the therapeutic benefits of leucocyte-platelet rich fibrin (L-PRF) as an adjunct to conservative surgical debridement of MRONJ in an out-patient setting. The microbiology of disease sites was also investigated. In addition, this study aimed to investigate the current trends in treatment strategies for MRONJ used by clinicians in the Republic of Ireland. Materials and methods Fourteen patients with a diagnosis of MRONJ were prospectively analysed specifically looking at clinical features, drug history, medical history, and social history to assess demographics and possible risk factors. The patients underwent conservative surgical debridement with adjunctive L-PRF at fifteen disease sites under local anaesthetic (+/- conscious intravenous dental sedation) in an outpatient theatre facility. Culture and sensitivity testing was performed for all cases. A questionnaire was designed and circulated to clinicians who were active in the diagnosis, and management of patients with MRONJ in secondary and tertiary care settings. The questionnaire explored aspects of what guidance clinicians apply to their practice, case-based scenarios on management, and their antibiotic prescribing protocols. Results In 93.3% (n=14) of disease sites there was a dental origin such as dental extraction or denture trauma identified as the initiating factor for MRONJ. Fourteen patients with fifteen disease sites were followed up for 6 months and curation was successful in 73.3% of disease sites (n=11). The microbes isolated from the samples were largely in keeping with the normal oral flora and sensitive to Penicillin. Similar microbes were isolated in oncology and osteoporosis patients, and in patients on bisphosphonates and RANK ligand inhibitors. The results of the questionnaire revealed no clear consensus on the management of MRONJ. The level of academic, and surgical training did not influence clinician?s treatment strategies to treat cases conservatively or surgically. There was no standardised consensus on the choice of antibiotic, route of administration, dosage, temporal pattern or duration of antibiotic prescribing for non-surgical treatment, or surgical treatment. Conclusion The results of this study indicate that local factors such as dental extractions and denture trauma play a role in the aetiology of MRONJ. Conservative surgical debridement with L-PRF is a successful treatment option in selected cases of MRONJ in an out-patient facility. Penicillin continues to provide suitable antibiotic coverage against the pathogens isolated from MRONJ disease sites. However, further evidence-based guidance is required to assist clinicians in the management of MRONJ cases.
APPROVED
Keywords: osteonecrosisof the jaws; maxillofacial surgery; bisphosphonates; denosumab